How CTML-based instructional video shapes students’ acceptance of asynchronous learning: an integrated TAM-TPB approach - Priyanto Priyanto; Ponco Walipranoto; Ahmad Chafid Alwi; Tinesa Fara Prihandini; Arif Ainur Rafiq (Journal of Education and Learning (EduLearn), 2026)
This study examines how the cognitive theory of multimedia learning (CTML)-based content quality shapes students’ acceptance of asynchronous learning within an integrated technology acceptance model (TAM)-theory of planned behavior (TPB) framework. The CTML provides the theoretical foundation for designing instructional videos that minimize cognitive load to enhance learning effectiveness. The proposed model links content quality to perceived usefulness and perceived ease of use, which influence attitude, subjective norm, perceived behavioral control, and behavioral intention. A quantitative approach using structural equation modeling (SEM) with SmartPLS was employed to analyze responses from 258 university students who had experienced asynchronous online learning. The results indicate that content quality significantly impacts perceived ease of use (β=0.589) and perceived usefulness (β=0.316). In turn, perceived usefulness significantly influences attitude (β=0.461) and behavioral intention (β=0.200), while attitude (β=0.171), subjective norm (β=0.381), and perceived behavioral control (β=0.156) also significantly predict behavioral intention. These findings validate the integrated TAM-TPB framework and demonstrate that CTML-based content quality functions as a cognitive antecedent of technology acceptance in higher education.